1998
DOI: 10.4315/0362-028x-61.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 in Full- and Reduced-Fat Pepperoni after Manufacture of Sticks, Storage of Slices at 4°C or 21°C under Air and Vacuum, and Baking of Slices on Frozen Pizza at 135, 191 and 246°C

Abstract: Pepperoni batter was prepared with fat contents of about 15, 20, and 32% (wt/wt) and inoculated with a pediococcal starter culture and > or = 2.0 x 10(7) CFU/g of a five-strain inoculum of Escherichia coli O157:H7. The batter was fermented at 96 degrees F (ca. 36 degrees C and 85% relative humidity (RH) to pH < or = 4.8 and then dried at 55 degrees F (ca. 13 degrees C) and 65% RH to a moisture/protein ratio of < or = 1.6:1. For storage, slices were packaged under air or vacuum and stored at 39 degrees F (ca. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Nadarajah (25) reported that the high levels of cis-oleic acid in beef fat may complex with the AIT molecules, producing a reduction in volatilization of AIT. Additionally, the high fat (low moisture) content of sausages has been reported to significantly reduce survival of E. coli O157:H7 in such products (13). A large reduction of E. coli O157:H7 numbers occurred during the first 3 days of fermentation in all treatments as a consequence of the rapid drop in pH.…”
Section: Resultsmentioning
confidence: 87%
“…Nadarajah (25) reported that the high levels of cis-oleic acid in beef fat may complex with the AIT molecules, producing a reduction in volatilization of AIT. Additionally, the high fat (low moisture) content of sausages has been reported to significantly reduce survival of E. coli O157:H7 in such products (13). A large reduction of E. coli O157:H7 numbers occurred during the first 3 days of fermentation in all treatments as a consequence of the rapid drop in pH.…”
Section: Resultsmentioning
confidence: 87%
“…The majority of studies enabled multiple inactivation rate estimates to be determined, providing a data set of 484 inactivation rates, encompassing over 50 E. coli strains and temperatures ranging from Ϫ20 to 66°C (mean ϭ 25.5°C), pHs ranging from 2.8 to 6.14 (mean ϭ 4.72), and a w values ranging from 0.75 to 0.986 (mean ϭ 0.901). Twenty-five (25) of the 484 inactivation rates were derived from biphasic inactivation curves and were based on the slowest phase of inactivation. The remaining 459 rates were from inactivation curves that were well described by single-phase inactivation models.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in a w during drying, storage, or heating was determined as the difference in a w measured at the end of the process and that at the end of fermentation. Three studies (4,5,25) reported a w at the end of drying or another postfermentation process but not at the end of fermentation. For those studies, a w at the completion of fermentation was assumed to be 0.96, which allowed additional data to be included in analyses of the total reduction in a w (19 data points) and the rate of reduction in a w (7 data points) during drying, storage, or heating.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations